2016
DOI: 10.1111/cea.12749
|View full text |Cite
|
Sign up to set email alerts
|

Important non‐disease‐related determinants of exhaled nitric oxide levels in mild asthma – results from the Swedish GA2LEN study

Abstract: Summary Background Fractional exhaled nitric oxide (FeNO) has a potential clinical role in asthma management. Constitutive factors such as age, height and gender, as well as individual characteristics, such as IgE sensitization and smoking, affect the levels of FeNO in population‐based studies. However, their effect on FeNO in subjects with asthma has been scarcely studied. Objective To study the effects on FeNO of these commonly regarded determinants, as demonstrated in healthy subjects, as well as menarche a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
4
12
2
Order By: Relevance
“…With regard to the relationship between lung function and airway inflammation, a more negative X5 associated in asthmatic individuals with higher FeNO 50 , a finding which is in line with previous studies . Classic lung function did not associate with FeNO 50 , and this corroborates the findings from a recent large study in adults, but contradicts our previous findings . The strength of the present study is that it is one of the largest studies to date to compare FOT and spirometry in both children and adults.…”
Section: Discussionsupporting
confidence: 87%
“…With regard to the relationship between lung function and airway inflammation, a more negative X5 associated in asthmatic individuals with higher FeNO 50 , a finding which is in line with previous studies . Classic lung function did not associate with FeNO 50 , and this corroborates the findings from a recent large study in adults, but contradicts our previous findings . The strength of the present study is that it is one of the largest studies to date to compare FOT and spirometry in both children and adults.…”
Section: Discussionsupporting
confidence: 87%
“…Taylor et al studied 895 healthy adults at age 32 years and found that men had approximately 25% higher F E NO levels than women (15.5 vs 11.6 ppb). A similar size of the sex difference has also been reported in asthmatic subjectsfor example, Al‐shamkhi et al reported that in 557 subjects with asthma from the Swedish GA2LEN study, men had 32% higher F E NO levels than women (24.0 vs 16.4 ppb). However, not all studies have been able to detect sex differences in F E NO .…”
Section: Discussionsupporting
confidence: 69%
“…In our study, F E NO levels were 21% higher in men than women (18.2 vs 15.0 ppb). Several previous studies have also reported an association between increased F E NO levels and male sex . Kim et al reported, based on data from 166 healthy Korean adults (aged 20‐68 years), that men had 27% higher F E NO levels than women (35.7 vs 26.0 ppb).…”
Section: Discussionmentioning
confidence: 97%
“…Finally, Al‐shamkhi et al have confirmed that the previously reported environmental and demographic factors that influence FeNO in healthy populations also apply to those with mild asthma. Two novel additional factors, age of menarche and parental smoking, also appear to lower FeNO in this population.…”
Section: Asthma and Rhinitismentioning
confidence: 58%